Potential Floristic Analysis of Peat Swamp Village Forest in Jambi Province to Supports Village Ecotourism Programme - Nursanti; Ulfa, Maria; Saleh, Zuhratus (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Pematang Rahim Village Forest is one of the social forestry schemes offered by the government. Pematang Rahim Village Forest Management Institute makes ecotourism as the basis for its management. Ecotourism in peat ecosystems in village forests creates biodiversity inside, especially plants, as the basis for planned ecotourism. The purpose of this research is to obtain data and information about the potential flora to support ecotourism-based village forest management. This study was carried out for 8 months from March to October 2021, located in the Village Forest of Pematang Rahim, East Tanjung Jabung Regency, and further analysis was conducted at the Herbarium and Laboratory of Management, Department of Forestry, Faculty of Agriculture, Jambi University. Research results in the field show that peat forests are generally managed as village forests in Pematang rahim in good condition. There are various types of trees and plants in different life forms. The study found 26 families, 58 genera, and 104 species, with a total of 2,831 individuals consisting of 855 seedlings, 880 saplings, 546 poles, and 550 trees. The diversity index showed a high value (> 3) for each growth stage from seedlings, sapling, pole to trees (3.39; 3.56; 3.65; 3.79). The existence of various peat-specific species with ecosystem conditions that are still maintained is expected to add value to ecotourism activities in the Pematang Rahim Village Forest area in the future.